2006
DOI: 10.1038/sj.npp.1301101
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Cocaine-Induced Behavioral Sensitization and Associated Phosphorylation of the NR2B and GluR1 Subunits of the NMDA and AMPA Receptors

Abstract: Cocaine abusers remain vulnerable to drug craving and relapse for many years after abstinence is achieved. We have recently shown that ondansetron (a 5-HT3 receptor antagonist) given 3.5 h after each daily cocaine injection reverses previously established behavioral sensitization. The purpose of the present investigation was two-fold. First, as cocaine cannot be used as therapy, we examined whether pergolide (a D1/D2 receptor agonist with reduced abuse potential) and ondansetron could reverse behavioral sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 56 publications
5
83
0
Order By: Relevance
“…Our previous studies have demonstrated that cocaine induces changes in expression and phosphorylated levels of the NR2B subunit of the NMDA receptors and the phosphorylated levels of GluR1 subunit of the AMPA receptors in the nucleus accumbens (NAc), and pergolide-ondansetron treatment normalizes these changes [3]. However, the mechanisms how a 5-HT 3 receptor antagonist influences NAc dopamine and glutamate transmission are unclear.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies have demonstrated that cocaine induces changes in expression and phosphorylated levels of the NR2B subunit of the NMDA receptors and the phosphorylated levels of GluR1 subunit of the AMPA receptors in the nucleus accumbens (NAc), and pergolide-ondansetron treatment normalizes these changes [3]. However, the mechanisms how a 5-HT 3 receptor antagonist influences NAc dopamine and glutamate transmission are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…on day 10. As either pergolide or ondansetron alone does not exert consistent effects on established cocaine sensitization and/ or associated molecular markers (3,5,18), the data from these treatment groups were not included in the present study.…”
Section: Experimental Groupsmentioning
confidence: 99%
See 3 more Smart Citations